Perilaku Bullying Antar Siswa Di Smp Negeri 23 Pekanbaru - Febriani, Lidya; Kadarisman, Yoskar (Jurnal Ilmiah Wahana Pendidikan, 2025)
Bullying is a serious problem for Indonesian education because almost all schools in Indonesia have bullying cases that cause mental trauma and often lead to death. bullying in the name of seniority is still very rampant among students from any level of education. This research aims to find out: 1) The forms of bullying behavior that occur in SMP Negeri 23 Pekanbaru, 2) The impact experienced by victims of bullying on students of SMP Negeri 23 Pekanbaru. This research used descriptive quantitative approach. The population in this study were all students of class VIII of SMP Negeri 23 Pekanbaru. The sampling technique used was purposive sampling technique by distributing questionnaires to the population, then obtained a research sample of 68 people. The results showed that the most dominant form of bullying was verbal bullying (61.8%), physical bullying (35.3%), then the last was psychological bullying (19.1%). The most common impact received by the victims was stress and depression, namely 16 respondents. While physical injuries amounted to 5 respondents, loss of goods amounted to 10 respondents, and felt traumatized coming to school amounted to 7 respondents, with this impact being less dominant. The level of bullying that has the most influence on the high and low impact received is verbal bullying with 42 respondents and physical bullying with 24 respondents. Meanwhile, psychological bullying is less dominant with 13 respondents.